Bi-allelic mutations in TRAPPC2L result in a neurodevelopmental disorder and have an impact on RAB11 in fibroblasts. Issue 11 (17th August 2018) - Milev, Miroslav P; Graziano, Claudio; Karall, Daniela; Kuper, Willemijn F E; Al-Deri, Noraldin; Cordelli, Duccio Maria; Haack, Tobias B; Danhauser, Katharina; Iuso, Arcangela; Palombo, Flavia; Pippucci, Tommaso; Prokisch, Holger; et al.
Abstract : Background: The combination of febrile illness-induced encephalopathy and rhabdomyolysis has thus far only been described in disorders that affect cellular energy status. In the absence of specific metabolic abnormalities, diagnosis can be challenging. Objective: The objective of this study was to identify and characterise pathogenic variants in two individuals from unrelated families, both of whom presented clinically with a similar phenotype that included neurodevelopmental delay, febrile illness-induced encephalopathy and episodes of rhabdomyolysis, followed by developmental arrest, epilepsy and tetraplegia. Methods: Whole exome sequencing was used to identify pathogenic variants in the two individuals. Biochemical and cell biological analyses were performed on fibroblasts from these individuals and a yeast two-hybrid analysis was used to assess protein-protein interactions. Results: Probands shared a homozygous TRAPPC2L variant (c.109G>T) resulting in a p.Asp37Tyr missense variant. TRAPPC2L is a component of transport protein particle (TRAPP), a group of multisubunit complexes that function in membrane traffic and autophagy. Studies in patient fibroblasts as well as in a yeast system showed that the p.Asp37Tyr protein was present but not functional and resulted in specific membrane trafficking delays. The human missense mutation and the analogous mutation in the yeast homologue Tca17 ablated the interaction between TRAPPC2L and TRAPPC10/Trs130, a component of the TRAPP II complex. Since TRAPP II activates the GTPase RAB11, we examined the activation state of this protein and found increased levels of the active RAB, correlating with changes in its cellular morphology. Conclusions: Our study implicates a RAB11 pathway in the aetiology of the TRAPPC2L disorder and has implications for other TRAPP-related disorders with similar phenotypes.